Motivasi Wisatawan Mancanegara Berkunjung Ke Taman Nasional Kelimutu, Kabupaten Ende, Provinsi Nusa Tenggara Timur - Quintas, Yudha Moses Diaz; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA; Vol 10 No 1 (2022): VOL 10, NO 1 (2022): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2022)
East Nusa Tenggara Province is one of the tourist destinations in Indonesia, by offering various kinds of tourism objects both natural attractions, beach tourism, and cultural tourism. One of the tourist destinations in East Nusa Tenggara that is rich in tourism objects and attractions is Kelimutu National Park Ende Regency, Flores, NTT, noted from the Kelimutu National Park Hall, that tourist visits continue to increase from 2014 to 2018, for the past five (5) years. From this it is an interesting thing to be used as a research entitled Motivation of Foreign Tourists Visiting Kelimutu National Park. With the aim of this study to obtain profiles and motivations of foreign tourists visiting the Kelimutu National Park. The method of this study uses data types namely qualitative and quantitative data (by carrying out 93 questionnaire distributions to foreign tourists). The results of this study are profiles of foreign tourists visiting Kelimutu National Park based on the Trip Descriptor and Tourist Descriptor which are seen from the characteristics of Socio demography, Geography, Psycography. Then the motivation of foreign tourists visiting the Kelimutu National Park is based on the types of tourists, namely Allocentric. Keywords : Tourist Motivation, Kelimutu National Park, East Nusa Tenggara